PEMANFAATAN CITRA LANDSAT UNTUK STUDI KARAKTERISTIK REFLEKTAN MANGROVE DI BENOA - Yuliara, Yuliara (BULETIN FISIKA; Vol 13 No 1 (2012): BULETIN FISIKA)
Have been carried out determining the characteristics of reflectance mangrove using data Landsat ETM +, with the study of the bay area Benoa, Bali. The results of the determination of the reflectance in the visible channels: the red channel is smaller than the blue and green channels. Value of reflectance at near infrared wavelengths at large, while in the middle infrared is smaller than on other vegetation, it indicates that the water content in leaf tissues of mangrove vegetation are more than the other. Graphic patterns representing the reflectance characteristics of mangrove showed a distinctive pattern in each channel. These patterns can be used to identify and distinguish objects with other objects mangrove (water, soil, vegetation non-mangrove).